Sex differences in predictive factors for onset of type 2 diabetes in Japanese individuals: A 15‐year follow‐up study. Issue 1 (6th October 2022) - Yoshimoto, Mei; Sakuma, Yukie; Ogino, Jun; Iwai, Rie; Watanabe, Saburo; Inoue, Takeshi; Takahashi, Haruo; Suzuki, Yoshifumi; Kinoshita, Daisuke; Takemura, Koji; Takahashi, Hidenori; Shimura, Haruhisa; et al.
Abstract: Aims/Introduction: The increase in the number of patients with type 2 diabetes mellitus is an important concern worldwide. The goal of this study was to investigate factors involved in the onset of type 2 diabetes mellitus, and sex differences in long‐term follow up of people with normal glucose tolerance. Materials and Methods: Of 1, 309 individuals who underwent screening at our facility in 2004, 748 individuals without diabetes were enrolled. Correlations of metabolic markers including serum adiponectin (APN) with onset of type 2 diabetes mellitus were examined over 15 years in these individuals. Results: The Kaplan–Meier curve for onset of type 2 diabetes mellitus for 15 years in the decreased APN group was examined. Hazard ratios for the APN concentration for onset of diabetes were 1.78 (95% confidence interval [CI] 1.20–2.63, P  = 0.004) in all participants, 1.48 (95% CI 0.96–2.29, P  = 0.078) for men and 3.01 (95% CI 1.37–6.59, P  = 0.006) for women. During the follow‐up period of 15 years, body mass index, estimated glomerular filtration rate, fatty liver, C‐reactive protein and alanine aminotransferase in men were significant in univariate analysis, but only estimated glomerular filtration rate and fatty liver were significantly related to onset of type 2 diabetes mellitus in multivariate analysis. In women, body mass index, systolic blood pressure, triglyceride, fatty liver and APN were significant in univariate analysis, and APN was the only significant risk factor in multivariate analysis ( P  < 0.05). Conclusions: There are differences between men and women with regard to targets for intervention to prevent the onset of type 2 diabetes mellitus. Individuals requiring intensive intervention should be selected with this finding to maximize the use of limited social and economic resources. Abstract : In women, adiponectin was the only significant risk factor for the onset of type 2 diabetes in multivariate analysis ( P  < 0.05). Therefore, there are differences between men and women with regard to targets for intervention to prevent the onset of type 2 diabetes mellitus. Individuals requiring intensive intervention should be selected with this finding to maximize the use of limited social and economic resources.